The Emergence (and Perils) of Income-Targeted Free Tuition - Usher, Alex (International Higher Education, 2017)
Free tuition has been implemented in many contexts, but is differently targeted, and can become more expensive and less effective than the policies it seeks to replace. New York, Chile, and Canada’s plans are highlighted in this article.